Educação socioambiental : percepções e proposições de processos educativos em Marau-RS - Poma, Silviani Teixeira (2009)
Nowadays environmental themes are among the most troublesome issues and not very used by many educators. This research is in line with the research of educational processes and language by trying to understand the significance of educational processes involving the socioenvironmental education established in the school environment and thematize them, as well as realize the diversity present in the relations established in this dynamic, new proposals will subsidize and methodological approaches to form the ecological citizen. So this study investigates how socioenvironmental education is perceived by teachers in final four years of fundamental education schools of Marau, based on a transversal perspective of socioenvironmental issues and with the central theoretical basis of deep ecology of Capra (2006a). To this end, we carried out a quantitative-qualitative analysis of data collected through a questionnaire answered by sixty teachers, along with an interview with nine of them. The questions were developed with the aim of investigating the perception of socioenvironmental education by the teachers, within sight simbiosynergic-inventive and the social pedagogy of self-development of Bertrand and Valois (1994). Based on data collected and analyzed, elaborated a proposal for an continued socioenvironmental education program to be used in all municipal schools in Marau